Implementasi Pembelajaran Bermakna di Madrasah untuk Meningkatkan Mutu Pendidikan Islam - Muhammad Yusran; Muhammad Nur Effendi; Hasan Hasan (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
The quality of Islamic education in Madrasahs depends significantly on the effectiveness of the learning process, which must address students' cognitive, affective, and psychomotor domains. However, reality shows that the learning process often falls into rote learning patterns. This study aims to analyze the implementation strategy of meaningful learning as a systematic effort to improve the quality of education in Madrasahs. The research method employed is library research using content analysis of the literature related to David Ausubel's cognitive theory and educational quality management. The results show that the strategy for implementing meaningful learning involves using advanced organizers, progressive differentiation, integrative reconciliation, and the utilization of the "amtsal" (parable) method derived from the Quran. The integration of religious subjects with contextual reality enables students to assimilate new knowledge into their existing cognitive structures more stably. The study concludes that the transformation from mere knowledge transfer to the internalization of meaning is the primary key to producing Madrasah graduates who are intellectually competent and possess deep spiritual awareness.